Peran Pekerja Sosial dalam Pengasuhan dan Perlindungan Anak : Studi Observasi di SOS Children's Village Medan - Christina Anugerah; Gloria Jesika Tampubolon; Vanessha Dini Olivia Sipayung; Fajar Utama Ritonga (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
Social Workers are a profession that has special skills in helping individuals, families, and communities to carry out their social functions optimally. One form of intervention carried out is through childcare, especially for children who are in a threatened condition or have lost care from the nuclear family. SOS Children's Village Medan implements a family-based care system that aims to create a safe, loving environment that supports children's holistic development. This study aims to determine the form of care carried out by social workers at SOS Children's Village Medan. The method used in this study is qualitative with a descriptive approach. The results of the study indicate that social workers play an important role in designing, supervising, and evaluating care patterns and accompanying children in meeting physical, emotional, social, and educational needs. The family approach has been proven to be able to build emotional bonds and improve the quality of life of the children being assisted.